La retórica de los personajes en Antígona de José Watanabe - Balvin Bernal, Bryan Jordy (2025)
This article will study the poetry collection Antígona (2000) by the Peruvian poet José Watanabe. This free version of Sophocles’ eponymous tragedy will be analyzed using the concepts of General Textual Rhetoric proposed by Giovanni Bottiroli (1993) and supplemented by Camilo Fernández (2011). The key concept for its application will be the rhetoric of the characters, specifically focusing on the two female characters of the tragedy: Ismene, the narrator, and Antigone. The main aim of this article is to demonstrate the predominant presence of the figure of thought known as antithesis in the poetry collection, and likewise, the way in which it becomes fundamental in the construction of the represented world and, consequently, of the selected characters.